2018
DOI: 10.1021/acs.jmedchem.8b01652
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of 5-(2,3-Dihydro-1H-indol-5-yl)-7H-pyrrolo[2,3-d]pyrimidin-4-amine Derivatives as a New Class of Receptor-Interacting Protein Kinase 1 (RIPK1) Inhibitors, Which Showed Potent Activity in a Tumor Metastasis Model

Abstract: We herein report the structural optimization and structure–activity relationship studies of 5-(2,3-dihydro-1H-indol-5-yl)-7H-pyrrolo­[2,3-d]­pyrimidin-4-amine derivatives as a new class of receptor-interacting protein kinase 1 (RIPK1) inhibitors. Among all obtained RIPK1 inhibitors, 1-(5-{4-amino-7-ethyl-7H-pyrrolo­[2,3-d]­pyrimidin-5-yl}-2,3-dihydro-1H-indol-1-yl)-2-[3-(trifluoromethoxy)­phenyl]­ethan-1-one (22b) is the most active one. This compound potently inhibited RIPK1 with a binding affinity (K D) of 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 33 publications
0
27
0
Order By: Relevance
“…RIPK1 has also been shown to regulate hematopoiesis (20)(21)(22), mediate inflammation (9,22), maintain chromosomal stability (23,24), and modulate the expression of immune checkpoint molecules such as PD-1 or PD-L1 (23), which are known to be upregulated in MDS after failure to hypomethylating agent (HMA) therapy (25). In addition, inhibition of RIPK1 has been hypothesized as a potential therapeutic mechanism in several malignancies (26,27).…”
Section: Introductionmentioning
confidence: 99%
“…RIPK1 has also been shown to regulate hematopoiesis (20)(21)(22), mediate inflammation (9,22), maintain chromosomal stability (23,24), and modulate the expression of immune checkpoint molecules such as PD-1 or PD-L1 (23), which are known to be upregulated in MDS after failure to hypomethylating agent (HMA) therapy (25). In addition, inhibition of RIPK1 has been hypothesized as a potential therapeutic mechanism in several malignancies (26,27).…”
Section: Introductionmentioning
confidence: 99%
“…69 noma lung metastasis model. 75 In other tumor models, knockout of RIPK1, RIPK3, or MLKL genes in cancer cells significantly reduced their tumorigenicity, and necroptosis inhibitors could slow tumor growth. In colon and esophageal cancer patients, it was also found that the level of MLKL phosphorylation was negatively correlated with prognosis and survival time.…”
Section: Necrop Tos Is and Mali G Nant S K In Tumormentioning
confidence: 99%
“…Although further studies are needed to elucidate the precise molecular mechanism through which RIPK1 and RIPK3 may mediate tumor cell extravasation, these observations reveal that RIPK1 and RIPK3 can be viewed as potential targets for developing therapeutic interventions against metastasis. Indeed, studies showed that blockage of RIPK1 kinase activity by Nec-1 or a different RIPK1 inhibitor significantly reduced tumor metastasis in vivo (Strilic et al, 2016;Li et al, 2018) (Table 1).…”
Section: Necroptosis In the Promotion Of Metastasismentioning
confidence: 99%